Pecahkan rekor skor tertinggi : The complete toefl CBT-IBT-PBT handbook / Haira Rizka, M. Furqon, Niswatin Nurul Hidajati ; penyunting, Nina Artanti R. - HAIRA RIZKA; Fuirqon, M.; Niswatin Nurul Hidajati; Nina Artanti R. (Pustaka Widyatama, 2016)
498 hlm. : ilus. ; 28 cm + CD